Human Resource Development in The Pandemic Context - Alina Natalia POP; Corina M. RADULESCU; Rita TOADER; Florina HAHN; Diana IGHIAN; Izabela RUS (Communications of International Proceedings, 2021)
This paper brings to the fore the importance of human resources as a value-creating force in the process of streamlining organizational activity, using several approaches in terms of critical analysis, comparative study, to conduct an analysis of human resource integration to current requirements. The development and implementation of an efficient system for vocational training, in correlation with market dynamics and real requirements, contributes to the development of human resources.
Keywords: Human Capital Development; Performance; Qualification